Comparison of Indonesian Banking Performance Pre and Post Pandemic Covid-19 - Anandhayu Mahatma Ratri; Agung Suwandaru; Harril Brimantyo; Ginanjar Indra Kusuma Nugraha; Almer Rasyid (Jurnal Bisnis dan Manajemen, 2022)
This research aims to determine and analyze the performance of Indonesia's Banking Sub Sector before and during the pandemic. We apply the CAMEL method to assess the Bank's performance via CAR (Capital Adequacy Ratio), NPL (Non-Performing Loan), NPM (Net Profit Margin), ROA (Return on Assets), and LDR (Loan to Deposit Ratio) in both situations. The sample uses 42 banking companies listed on the Indonesia Stock Exchange from 2019 – 2020. The results show that the CAR, NPL, and NPM values during the pandemic have increased compared to before the pandemic. However, the ROA and LDR values decreased during the pandemic compared to before the pandemic. The other findings exhibit no significant differences in CAR, NPL, NPM, ROA, and LDR on bank performance before and during the pandemic. In conclusion, banks should be aware of changes during the pandemic and will change various financial transactions. The research results are also significant for policymakers to make policies that can facilitate the community and the banking world in the post-pandemic era by paying attention to changes.